Digital Workflow for the Design, Manufacture, and Application of Custom-Made Short Implants With Wing Retention Device - Xu, Zexian; Yang, Zhen; Yang, Jianjun (Frontiers in Bioengineering and Biotechnology, 2022)
The severe deficiency of vertical bone height in the posterior maxillary region poses a challenge to implant restoration. In response to this issue, this article introduces a custom-made short implant with a wing retention structure, and describes a precise and minimally invasive dental implant restoration scheme with digital technology.